Average Error: 0.0 → 0.0
Time: 7.9s
Precision: 64
$\sqrt{x + 1} + \sqrt{\sqrt{x + 1}}$
$\sqrt{x + 1} + \sqrt{\sqrt{x + 1}}$
\sqrt{x + 1} + \sqrt{\sqrt{x + 1}}
\sqrt{x + 1} + \sqrt{\sqrt{x + 1}}
double f(double x) {
double r3630006 = x;
double r3630007 = 1.0;
double r3630008 = r3630006 + r3630007;
double r3630009 = sqrt(r3630008);
double r3630010 = sqrt(r3630009);
double r3630011 = r3630009 + r3630010;
return r3630011;
}


double f(double x) {
double r3630012 = x;
double r3630013 = 1.0;
double r3630014 = r3630012 + r3630013;
double r3630015 = sqrt(r3630014);
double r3630016 = sqrt(r3630015);
double r3630017 = r3630015 + r3630016;
return r3630017;
}



Try it out

Results

 In Out
Enter valid numbers for all inputs

Derivation

1. Initial program 0.0

$\sqrt{x + 1} + \sqrt{\sqrt{x + 1}}$
2. Final simplification0.0

$\leadsto \sqrt{x + 1} + \sqrt{\sqrt{x + 1}}$

Reproduce

herbie shell --seed 1
(FPCore (x)
:name "sqrt(x+1) + sqrt(sqrt(x+1))"
:precision binary64
(+ (sqrt (+ x 1)) (sqrt (sqrt (+ x 1)))))